MINIMISASI LIMBAH INDUSTRI KULIT MELALUI OPTIMASI PRODUKSI - Hidayah, Euis Nurul (Jurnal Teknik Kimia, 2007)
Applicaton of waste minimizing can be executed through effort of production optimizing thatis implemented through Recycling, Reuse and or Recovery. In the hierarchy of wastemanagement, waste minimizing is the primary strategy in management of waste. Finding approachof management of waste which is able to suppress the amount of wastes yielded by husk industryproduct process of Magetan as optimal as possible, so that in the end can create a management ofenvironment that able to prevent the happening of damage of environment.Existence of optimation of chemicals usage in UD Sumber Kulit quality of yielded waste waterbefore optimation with rate = 90,09 mg / lt and COD = 225,4 mg / lt, after optimation was donequality of yielded waste water go down for BOD = 80,75 mg / lt and COD = 204,77 mg / lt. Withdegradation efficiency for BOD = 9,34 % and COD = 20,63 %.Execution effort of waste minimization of each production process through optimalizing ofusage of chemicals such as : prasoaking and soaking of NaOH 0,25 %, max rate = 0,1 - 0,2 %.effort of optimation 0,05% and Na2S liming 4,5 %, max rate = 2 - 4 %. effort of optimation = 0,5% from raw husk weight ± 8,64 excessive weight.Keywords : waste minimitation, optimation, waste of husk